A practical approach to demonstrate the circular economy in remediation of textile dyes using nutraceutical industrial spent - Taqui, Syed Noeman (2024)
Funding Information: The authors would like to acknowledge the support provided by Researchers Supporting Project Number RSP2024R424, King Saud University, Riyadh, Saudi Arabia. Publisher Copyright: © 2024 The Royal Society of Chemistry.